Asian experiences of developing enterprises with foreign participation in the renewable energy market - A. I. Dudnik (Вестник университета, 2025)
The article discusses the main trends and patterns in the development of entrepreneurial projects with foreign participation in the renewable energy market on the international stage. It identifies the factors that contribute to the successful growth of such enterprises and assesses the potential for applying foreign experience to the Russian energy sector. The relevance of the study is driven by the significant increase in foreign investments in clean energy worldwide. However, only a few countries have created favourable conditions for foreign investors, which affects the overall efficiency of the renewable energy market. The purpose of the work is to analyse successful foreign practices in the countries comparable to Russia (India and China) concerning the development of joint entrepreneurial projects in the clean energy sector. To achieve the research objectives, the following methods have been used: content analysis of scientific literature and legal documents, cross-national comparative analysis, and qualitative research methods, including expert interviews and case studies. As a result, key mechanisms of interest for adaptation to Russian realities are systematised, and the role of integrating international practices into the energy context of Russia is highlighted. In conclusion, the author proposes an integrated approach for introducing the successful foreign practices into the institutional environment of the Russian green energy market.